(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of medical incident reporting at Kien An Hospital in 2022- 2023. Methods: Cross-sectional descriptive study, secondary data analysis. Results: 110 medical incident reports (SCYK), of which 71.8% were voluntary reports; The Department of Gastroenterology and the Department of Surgical Anesthesia reported SCYK the most at 13.6%; Nurses, technicians, and midwives reported 70.9% of incidents; The level of injury caused by the incident directly affecting the patient and not causing harm is 39.1%; The group performing technical procedures and professional procedures accounts for the highest proportion of 33.6%; The group that causes the most incidents is the group of medical staff, 61.8%. Conclusion: During the implementation process, there are still many medical incidents that are not voluntarily reported to the system. It is also recommended that Faculty/Department Leaders must regularly monitor and remind staff to comply with SCYK reporting regulations. Health workers need to actively and proactively report medical conditions and comply with regulations on medical emergency reporting.